In the tall, tall grass - Fleming, Denise, 1950- (New York : H. Holt, 1991)
Rhymed text (crunch, munch, caterpillars lunch) presents a toddler's view of creatures found in the grass from lunchtime till nightfall, such as bees, ants, and moles
Keywords: Animals -- Juvenile literature; Stories in rhyme